Annonce d’acte de conférence - Trébuchon, Jean-François (BOIS & FORETS DES TROPIQUES, 2023)
All-Division 3 Conference and 44th Council on Forest Engineering 107 and 54th International Symposium on Forestry Mechanization: One big family - Shaping the future together. 4-7 October 2022. Corvallis, Oregon, United States. All-IUFRO Conference: Forests in a Volatile World Global Collaboration to Sustain Forests and Their Societal Benefits. 21-23 September 2022. University of Applied Arts ("Die Angewandte"), Vienna, Austria.